Organizational leadership factors lead to employee engagement in BP Solution Company, Johor - Nur Izzatul Adila Tajudin, author; Nur Naha Abu Mansor, supervisor; Fakulti Pengurusan dan Pembangunan Sumber Manusia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2011)
Project Paper (Sarjana Muda Psikologi) - Universiti Teknologi Malaysia, 2011